THE TRANSLATION OF DEMONSTRATIVE REFERENCES FROM ENGLISH INTO INDONESIAN IN THESIS ABSTRACTS IN STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - NURASIETA, AJENG FAJRIANI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Translation, Thesis, Thesis Abstract, Demonstrative References. Translator’s ability to translate cohesive device from one language to another would help in maintaining cohesion of a text. The cohesive device that was analyzed in this research was demonstrative references. The objectives of this research are: (1) to discover the types of demonstrative references used in the thesis abstracts written by students of Study Program of English and (2) to investigate how the demonstrative references was translated into Indonesian.Qualitative approach was used in conducting this research. The data of this research were the demonstrative references translated from English into Indonesian found in 10 thesis abstracts written by students in Study Program of English. The researcher set several criteria to select the data source, then the researcher made a copy of the abstracts, highlighted and listed the demonstrative references. Then the data were analyzed by classifying the findings based on the classification of English demonstrative references proposed by Halliday and Hasan (1976), analyzing the findings by using the theory proposed by Suryawinata (1989), and the last drawing conclusion.The researcher found 256 occurrences of demonstrative references in the abstracts. The demonstratives found were this¸ that, these, those, the, here, and then. From the findings, it was found that the demonstratives were translated to match the context in which they appeared. However, there were some changes needed in order to make the translation become more natural for the target readers.Based on the analysis and discussion, the researcher concluded that the translators had understood the concept of meaning. This research could still be developed by analyzing other types of cohesive devices and using different objects. The researcher hoped that the future researcher would be able to conduct a research on related topic with the current research and find interesting results that differ from the current research.